Legal Analysis of Copyright Dispute Resulution in the Creative Industries in the Digitalization Era - Christina Bagenda; Markus Suryoutomo; Bambang Supriadi; Agnes Maria Janni Widyawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Copyright protection faces additional difficulties as a result of the creative industry's rapid development and growing digitalization. Large-scale copyright infringement result from the open and accessible nature of the internet, which permits the unapproved reproduction and distribution of creative works. In the digital age, resolving copyright disputes has become essential to creating a system that safeguards authors' rights and promotes the expansion of the creative sector. The purpose of this essay is to examine the legal ramifications of settling copyright disputes in the digital age creative business, as well as to pinpoint the difficulties encountered and workable remedies. This study examines the current dispute settlement procedures under Indonesian law using an analytical legal methodology. The study is anticipated to shed more light on how the law handles copyright disputes and make suggestions for enhancing copyright protection online.